(untitled) (World Bulletin of Social Sciences, 2023)
The formation of reading skills is recognized as one of the most important stages of language teaching. Reading is a skill that is distinguished by the achievement of students according to their mastery. It is one of the most complex mental activities and involves thinking and understanding more problems by anticipating the symbolic meanings of words and analyzing and checking conclusions. In this process, it is observed that learners think differently based on their thinking.